2016
DOI: 10.1002/asia.201600445
|View full text |Cite
|
Sign up to set email alerts
|

Solvent‐Regulated Asymmetric Hydrogenation of Quinoline Derivatives in Oligo(Ethylene Glycol)s through Host–Guest Interactions

Abstract: The asymmetric hydrogenation of quinolines in oligo(ethylene glycol)s (OEGs) and poly(ethylene glycol)s (PEGs) with chiral cationic ruthenium diamine complexes has been investigated. Interestingly, in liquid PEGs or long-chain OEGs, the Ru catalysts lost their reactivity. Upon the addition of a little MeOH, the hydrogenation of quinoline was switched "ON". Evidence from mass spectrometry and control experiments revealed that encapsulation of the quinolinium salt by PEG or long-chain OEG molecules through supra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…The asymmetric hydrogenation of quinolines was also achieved in oligo­(ethylene glycol)­s (OEGs) and poly­(ethylene glycol)­s (PEGs) in the presence of Ru­(TsDPEN) catalyst in excellent yields and enantioselectivities . The recycling of the catalyst was demonstrated both in pure 3-OEG and in a biphasic 3-OEG/ n -hexane system.…”
Section: Synthesis Of 1234-tetrahydroquinolines By Partial Hydrogenat...mentioning
confidence: 99%
“…The asymmetric hydrogenation of quinolines was also achieved in oligo­(ethylene glycol)­s (OEGs) and poly­(ethylene glycol)­s (PEGs) in the presence of Ru­(TsDPEN) catalyst in excellent yields and enantioselectivities . The recycling of the catalyst was demonstrated both in pure 3-OEG and in a biphasic 3-OEG/ n -hexane system.…”
Section: Synthesis Of 1234-tetrahydroquinolines By Partial Hydrogenat...mentioning
confidence: 99%
“…Recycling of expensive chiral catalysts is crucial to practical applications. Fan and co-authors [13,15] attempted to recycle the homogeneous catalyst, Ru/Ts-DPEN, via a liquid-liquid phase separation method, in which the products were extracted by n-hexane and the catalyst remained in the solvent after the reaction; examples of such solvents include ionic liquids (ILs) or short-chain triethylene glycol. The complicated separation process led to the wastage of solvent and consequent increased costs.…”
Section: Introductionmentioning
confidence: 99%
“…The same authors reported that similar Ru-diamine complexes were capable of efficiently hydrogenating S127a in solvent-free conditions, 445 in neat water, 446 in ionic liquids, 447,448 and in oligo(ethylene glycol)s through host−guest interactions. 449 On the other hand, the AH of 2-aryl-substituted quinolines was more challenging, and only a few examples have been reported. The same group extended the use of these Ru(II)−diamine complexes and found that C14h was a highly active catalyst for the AH of 2-aryl quinolines, affording the corresponding P127a (R = aryl) in excellent yields and enantioselectivities (Scheme 85).…”
Section: Quinolines and Derivativesmentioning
confidence: 99%
“…In contrast, the AH of 2,3-dialkyl quinolines S127b provided a very low ratio of diastereoselectivity. The same authors reported that similar Ru-diamine complexes were capable of efficiently hydrogenating S127a in solvent-free conditions, in neat water, in ionic liquids, , and in oligo­(ethylene glycol)­s through host–guest interactions . On the other hand, the AH of 2-aryl-substituted quinolines was more challenging, and only a few examples have been reported.…”
Section: Asymmetric Hydrogenation Of Heteroaromatic Compoundsmentioning
confidence: 99%